Private sport finance in Finland: New socially responsible financing for individual athletes - Hirvonen, M. (Jyväskylä University of Applied Sciences, 2024)
This master's thesis dives into the shifting landscape of sports financing in Finland, emphasizing the historical reliance on state funding, particularly through Veikkaus Oy, the state-owned gambling monopoly. Many factors have resulted in diminished financial support for athletes and sports in Finland. To address this, new private funding entities have emerged.